2019
DOI: 10.1111/1742-6723.13339
|View full text |Cite
|
Sign up to set email alerts
|

Emergency first aid readiness in Antarctica: Australian Antarctic expeditioners’ first aid credentials and self‐efficacy

Abstract: Introduction To help prevent future morbidity and mortality, this study examined Australian Antarctic expeditioners’ first aid credentials and self‐efficacy in providing emergency first aid in extreme environments. Methods A mixed method survey assessed Australian personnel working on Antarctic stations. Volunteer participants (n = 83) provided data on first aid training, self‐confidence of first aid readiness, and first aid preparations. The Extreme Conditions First Aid Confidence Scale (EC‐FACS) was develope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 28 publications
0
1
0
1
Order By: Relevance
“…Respon cepat dan tepat dalam memberikan BHD dapat meningkatkan peluang kelangsungan hidup korban kejadian darurat medis (Kementerian Kesehatan Republik Indonesia, 2011). Setiap detik sangat berharga, dan masyarakat yang terlatih dapat memberikan pertolongan pertama sebelum bantuan medis profesional datang (Wallace, Harris, Stankovich, Ayton, & Bettiol, 2020).…”
Section: Pendahuluanunclassified
“…Respon cepat dan tepat dalam memberikan BHD dapat meningkatkan peluang kelangsungan hidup korban kejadian darurat medis (Kementerian Kesehatan Republik Indonesia, 2011). Setiap detik sangat berharga, dan masyarakat yang terlatih dapat memberikan pertolongan pertama sebelum bantuan medis profesional datang (Wallace, Harris, Stankovich, Ayton, & Bettiol, 2020).…”
Section: Pendahuluanunclassified
“…In particular, for our study, the importance of high self-efficacy for successful adaptation and work in the Antarctic station can be determined by the fact that this property ensure an individual's capacity to exercise control over the nature and quality of one's life (Bandura 1997) and that self-efficacy means a belief in one's competence and capability to solve problems and execute actions to manage life situations (Slone et al 2013). The recent studies performed by Wallace et al (2020) indicated the great importance of high self-efficacy for participants in Antarctic expeditions.…”
Section: Introductionmentioning
confidence: 98%